Modern ideas about the role of the hypothalamus in the implementation of adaptation programs under stressor loads (references) - Romanova, K.; Hancheva, O. (Journal of Education, Health and Sport, 2022)
The starting point for the prevention of human disease is the study of the vital functions of a healthy organism, taking into account complex effects of external and internal factors. More often in clinical practice, doctors observe patients with advanced pathology, when the body has undergone significant changes, including at the level of systemic regulation (CNS, hypothalamus) and at the level of intercellular signaling and neuro-immune-endocrine interactions. Therefore, the basis of these changes, more often, are insignificant but permanent factors of the external or internal environment, which gradually accumulate and disrupt the functioning of central regulatory systems. The aim of our study was to analyze modern sources of information that highlight current issues of the role of the hypothalamus in the development of adaptation programs during the formation of stressors. Materials and methods: analysis of scientific publications taken from Google Scholar databases, Web of Science, Pub Med by keywords: rats, stress reactions, adaptation, neuroendocrine regulation, neurotransmitters, hypothalamus, supraoptic nucleus, paraventricular nucleus. Conclusions: Thus, the analysis of scientific sources demonstrated that the main stress studies were devoted to determining the state and role of dominant systems, but there were few facts that had explained the long-term changes of the hypothalamus in regulatory systems. These issues remain unresolved and need to be studied. Introduction. Today, many facts and clinical observations about the complex effects of chronic stress of human body. The National Institutes of Health and the U.S. Veterans Health Administration conducted a large-scale cohort study that had provided evidence of an association between post-traumatic stress disorder and cardiovascular risk, had identified mechanisms that could cause this association, and had assessed prognostic risk, cardiovascular diseases [1]. Moreover, they form a post-stress syndrome, which by itself becomes a pathogenetic mechanism of disease formation. Rebeca Robles-García together with other researchers in 2020 demonstrated that high urbanization could increase the risk of post-traumatic stress disorder due to the concentration of poverty, limited living space, substance use and crime. Women tend to be more disadvantaged socially and economically and are more likely to be victims of collective and domestic violence than men. Accordingly, urban women are more prone to traumatic events that increase the prevalence of post-traumatic stress disorder than rural women and men in both rural and urban areas, especially those without social and family protection and support [2]. That is, even minor and indistinct stressors that act constantly and can not be overcome by man become an important etiological factor in the formation of a number of diseases.